THE INFLUENCE OF THE FILM 'RUDY HABIBIE' ON THE INCREASE IN LEARNING INTEREST AMONG ADOLESCENTS - Alfiyah, Nurmaya; Widiasanty, Gita (Transpublika Publisher, 2023)
Broadcast media can be found in everyday life as an important source in providing information, education, art and various other things. Information technology is developing rapidly. One technology that can be a medium for disseminating information and messages is film media. Film is a broadcasting technology that can provide a moral message in the film. Films can convey a message through audio visuals. The film taken from this research is Rudy Habibie's film. This study aims to prove whether or not there is an influence from Rudy Habibie's film on the increasing interest in learning in adolescents. This research uses quantitative and is carried out by distributing questionnaires that have been made using GoogleForm. The population is teenagers in the RW. 02 Kelurahan Cipedak, South Jakarta, which has been determined to have watched the Rudy Habibie film. Sampling was done by non-probability sampling. The variables in this study are teenagers who have watched the Rudy Habibie film. The results showed that Rudy Habibie's film had a positive and significant effect on increasing student interest in learning. Then H1 is accepted H0 is rejected. This means that Rudy Habibie's film can influence interest in learning in adolescents. The results are based on the distribution of questionnaires that have been filled out by the youth.